BRAF Mutation Status and Histopathological Differentiation Patterns in Non–Small Cell Lung Cancer: A Tertiary Referral Center Study in Indonesia - Lela Khaibirunna A.P; Noni Novisari Soeroso; Desfrina Kasuma; Putri Eyanoer (CoinReads Media Prima, 2026)
Introduction: Non-small cell lung cancer (NSCLC) is the most common subtype of lung cancer and a major cause of cancer-related mortality worldwide. BRAF mutations have emerged as clinically relevant molecular alterations associated with tumor behavior and targeted therapy responses. However, evidence regarding their relationship with histopathological differentiation remains limited, particularly in the Indonesian population. This study aimed to evaluate the association between BRAF mutation status and histopathological differentiation in patients with NSCLC at a tertiary referral center in Indonesia. Methods: This retrospective cross-sectional study included patients diagnosed with NSCLC at a tertiary hospital in Medan, Indonesia. Clinical and demographic data were obtained from patients’ medical records. Histopathological differentiation was classified as well-, moderately, or poorly differentiated. BRAF mutation analysis was performed using real-time polymerase chain reaction on formalin-fixed paraffin-embedded tissue samples. Statistical analyses were performed to determine the association between BRAF mutation status and histopathological differentiation. Results: Most patients were men (76.7%), aged >40 years, and had a history of smoking (74.2%). Adenocarcinoma was the predominant histological subtype (75%), and most patients were diagnosed at stage IVA (60%). BRAF mutations were identified in 3.3% of the patients. Histopathological evaluation revealed that 20.8%, 37.5%, and 41.7% of the tumors were well-, moderately-, and poorly differentiated, respectively. A significant association was observed between BRAF mutation status and histopathological differentiation (P = 0.001), with mutations being more frequently detected in poorly differentiated tumors. Conclusion: BRAF mutations were identified in a small proportion of NSCLC patients and were significantly associated with poor histopathological differentiation, suggesting a potential role in aggressive tumor biology.